2013
DOI: 10.1111/tan.12183
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of variability for 18 immune system genes in Amerindians – relationship with history and epidemiology

Abstract: Native American populations generally have a higher prevalence of infectious diseases than non-Native populations and this fact can induce different pressures in their immune system. We investigated the patterns of population differentiation (FST ) of 32 polymorphisms related to adaptive immune response in four Native American populations (Aché, Guarani-Kaiowá, Guarani-Ñandeva and Kaingang), and the results were compared with the three major world population data [Yoruba of Ibadan, Nigeria (YRI), Utah resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…The CHB population has been shown to have similar allele frequencies to Native Americans. [11][12][13] In addition, 64 individuals from different indigenous tribes in Latin America of the HGDP-CEPH Diversity Panel (NAM) were used as Amerindian reference population with 108 markers common to all data sets. 14 For Structure analyses, the admixture model was employed assuming correlated population allele frequencies with a burn-in period of 10 000 and 100 000 iterations.…”
Section: Discussionmentioning
confidence: 99%
“…The CHB population has been shown to have similar allele frequencies to Native Americans. [11][12][13] In addition, 64 individuals from different indigenous tribes in Latin America of the HGDP-CEPH Diversity Panel (NAM) were used as Amerindian reference population with 108 markers common to all data sets. 14 For Structure analyses, the admixture model was employed assuming correlated population allele frequencies with a burn-in period of 10 000 and 100 000 iterations.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations reported that Native American populations have a lower variability in several immune system genes such as KM, GM, Kell, HLA, and KIR (Bhatia et al, 1995;Black and Pandey, 1997;Black, 2004;Prugnolle et al, 2005;Augusto et al, 2013Augusto et al, , 2015. Recently it has been reported that the pattern of adaptive immune system variability in Amerindians populations differs from that observed in the HapMap CEU population as evaluated by F ST analyses (Lindenau et al, 2013). It is well established that environmental exposure to parasites, helminths, and physical injuries were very different during the evolutionary histories of world populations, leading to differences in immune response patterns observed among these groups (Finkelman and Urban, 2001;Hurtado et al, 2003;Lazzaro and Little, 2009;Schulenburg et al, 2009;Cagliani and Sironi, 2013).…”
mentioning
confidence: 99%
“…Low diversity was observed in South Native American populations for several genetic markers, among them HLA, KIR, and microsatellites [4][5][6]12]. The Aché population was the one with the lowest observed heterozygosity among the Native American populations studied for the above mentioned markers.…”
Section: Discussionmentioning
confidence: 90%
“…This differential susceptibility is usually explained by the nontraditional variability in the HLA/KIR, adaptive and innate immune systems genes [4][5][6][7]. The reduced variability in the HLA system was associated with higher purified protein derivative skin test response (PPD) reaction in the Aché population [8].…”
Section: Introductionmentioning
confidence: 98%